EU member state participation in military operations: a configurational comparative analysis. Issue 2 (4th March 2017) - Haesebrouck, Tim
Abstract: Contrary to what the EU's image as a civilian power suggests, the EU member states have had 50, 000–100, 000 troops deployed outside their home countries for most of the post-Cold-War period. Although the vast majority of these troops were active in operations with a strong European presence, the member states' patterns of military engagement differ significantly. This study provides a systematic analysis of the member states' contributions to military operations. More specifically, it examines which (combinations of) conditions consistently led to participation in EUFOR Congo, UNIFIL II, EUFOR Chad, the 2011 military intervention in Libya and the air strikes against the Islamic State. Methodologically, it builds on most different similar outcome/most similar different outcome and qualitative comparative analysis. The results of the analysis show that four conditions account for the bulk of the member states' patterns of military engagements: military resources, competing deployments, UN peacekeeping tradition and regional trade.